2007
DOI: 10.4049/jimmunol.178.9.5571
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Infiltrating CD8+ T Cells Initiate Atopic Dermatitis Lesions

Abstract: Skin lesions in the allergic form of atopic dermatitis (AD) are induced by allergen-specific T cells that infiltrate the skin at the site of allergen exposure. Although Th2-type CD4+ T cells appear to be crucial in AD pathophysiology, little is known about the contribution of CD8+ T cells in the development of the allergic skin inflammation. In the present study, we have analyzed the respective role of CD8+ and CD4+ T cells in the development of AD skin lesions in a mouse model of allergen-induced AD. In sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 31 publications
5
79
0
4
Order By: Relevance
“…When kept under specific pathogen-free (SPF) conditions, these mice remain normal and healthy. However, when placed in conventional surroundings, clinical signs including scratching behavior appear and IgE levels are elevated from the age of 8 weeks [22,23]. Thus, NC/Nga mice are often used as a sensitive animal model for human AD.…”
Section: Introductionmentioning
confidence: 98%
“…When kept under specific pathogen-free (SPF) conditions, these mice remain normal and healthy. However, when placed in conventional surroundings, clinical signs including scratching behavior appear and IgE levels are elevated from the age of 8 weeks [22,23]. Thus, NC/Nga mice are often used as a sensitive animal model for human AD.…”
Section: Introductionmentioning
confidence: 98%
“…Allergic contact dermatitis (ACD) caused by metallic ions and other reactive haptens is a T cell-mediated inflammatory skin disease (4)(5)(6). ACD is characterized by two phases: a sensitization phase and an elicitation phase.…”
mentioning
confidence: 99%
“…7). Recently, it was shown that allergen-primed CD8 + T cells are required for the development of AD skin lesions in mice [38]. In the present study, RA significantly reduced skin lesion infiltration by CD8 + T cells, but in mouse and rat models, allergic inflammation was found to be dependent on CD4 + T cells, and CD8 + T cells were found to have a negative regulatory effect [39,40].…”
Section: Discussionmentioning
confidence: 57%